1978
DOI: 10.1115/1.3446382
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling of a Gas Turbine Blade

Abstract: The local film-cooling produced by a row of jets on a gas turbine blade is measured by a mass transfer technique. The density of the secondary fluid is from 0.75 to two times that of the mainflow and the range of the mass flux ratio is from 0.2 to three. The effect of blade-wall curvature on the film-cooling effectiveness is very significant. On the convex wall, a near tangential jet is pushed towards the wall by the static pressure force around the jet. For a small momentum flux ratio, this results in a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(61 citation statements)
references
References 0 publications
7
52
2
Order By: Relevance
“…The verification of such statement may be given when the results of studies that have investigated the effect of curvature and such, present in airfoil types of configuration, are reviewed, e.g. Mayle et al [38], Ito et al [39] and Davidson et al [40].…”
Section: Computational Fluid Dynamics Studiesmentioning
confidence: 99%
“…The verification of such statement may be given when the results of studies that have investigated the effect of curvature and such, present in airfoil types of configuration, are reviewed, e.g. Mayle et al [38], Ito et al [39] and Davidson et al [40].…”
Section: Computational Fluid Dynamics Studiesmentioning
confidence: 99%
“…The Heat Transfer Laboratory has investigated film cooling effectiveness using the foreign gas injection method through ondtwo rows of film cooling holes on convex/concave surfaces and turbine blades (Schwan andGoldstein, 1988 andIto, Goldstein andEckert, 1978). Results show that the blade surface curvature influences the f i l m cooling effectiveness particularly in the vicinity of the injection holes, with higher effectiveness on the convex surface, lower on the concave surface, as compared to a flat plate case.…”
Section: Surface Measurementsmentioning
confidence: 99%
“…Ito et al (1978) found that an increase in coolant-to-mainstream density ratio causes an increase in film effectiveness on both pressure and suction surfaces for a blowing ratio of 1.0. Haas et al (1992) found that their results show the same trends as that of Ito et al (1978). They reported that an increase in coolant density for a low blowing ratio of 0.5 causes a decrease in film effectiveness on the suction surface.…”
Section: Introductionmentioning
confidence: 99%
“…Takeishi et al (1992) compared the film effectiveness values for a stationary cascade with mainstream turbulence intensity under 4% and for a rotor blade using the heat-mass transfer analogy. Ito et al (1978) and Haas et al (1992) studied the effect of coolant density on film effectiveness on turbine blades under low mainstream turbulence levels. Ito et al (1978) found that an increase in coolant-to-mainstream density ratio causes an increase in film effectiveness on both pressure and suction surfaces for a blowing ratio of 1.0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation